2019
DOI: 10.5539/gjhs.v11n9p134
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Amateur Bodybuilding Athletes Around Polokwane Municipality in Limpopo Province, South Africa

Abstract: Objective:To determine the dietary intake of amateur bodybuilding athletes around Polokwane municipality in Limpopo Province, South Africa.Design: This was a descriptive cross-sectional study in which purposive sampling was used to recruit 51 participants out of 65 registered part-time competitive bodybuilders at three training gyms around Polokwane. Dietary information was collected using a modified 24-hour-recall questionnaire on three different days, which was validated by the modified Food Frequency Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…This may predispose them to nutritional deficiencies and later health hitches, such as bone problems whenever continuing in this sport. Therefore, the involvement of dietetic/nutrition practitioners within existing team members, such as coaches and trainers, may assist this group in nutrition guidance for instance; diet plans, body composition, and weight monitoring [23]. The researchers are aware that the findings of this study cannot be generalized given the smaller sample size.…”
Section: Conclusion and Recommendationmentioning
confidence: 98%
“…This may predispose them to nutritional deficiencies and later health hitches, such as bone problems whenever continuing in this sport. Therefore, the involvement of dietetic/nutrition practitioners within existing team members, such as coaches and trainers, may assist this group in nutrition guidance for instance; diet plans, body composition, and weight monitoring [23]. The researchers are aware that the findings of this study cannot be generalized given the smaller sample size.…”
Section: Conclusion and Recommendationmentioning
confidence: 98%
“…A similar intake of energy below recommended values was reported by Jenner et al [21] among Australian soccer athletes. Another study in Limpopo province reported the same findings among the athletes, although the focus of this study was on a different group of athletes, bodybuilders [22]. However, in another study by Steffl et al [23], adequate energy intake was reported among athletes.…”
Section: Demographymentioning
confidence: 54%
“…Nutritional information sources such as coaches and/or media may at times offer inconsistent or deviating evidence-based practices [37] posing a threat to the health outcomes of athletes. For instance, in a study by Masoga et al, macronutrients intake by bodybuilding athletes around PM was reported suboptimal [7]. It is possible that the type of nutrition information source used by the majority of bodybuilders in the latter study guided them toward intakes that deviate from sports nutrition science.…”
Section: Nutrition Information Sourcesmentioning
confidence: 97%
“…Although the use of ergogenic substances among young athletes is not encouraged, there seems to remain an increased use of these substances by athletes [5]. The dietary intake of bodybuilding athletes around the PM has been reported [7]. However, practices related to the use of ergogenic substances have not been comprehensively covered.…”
Section: Introductionmentioning
confidence: 99%